A Metagenomic Investigation of the Duodenal Microbiota Reveals Links with Obesity. - Emmanouil Angelakis; Fabrice Armougom; Frédéric Carrière; Dipankar Bachar; René Laugier; Jean-Christophe Lagier; Catherine Robert; Caroline Michelle; Bernard Henrissat; Didier Raoult (PLoS ONE, 2015)
Few studies have tested the small intestine microbiota in humans, where most nutrient digestion and absorption occur. Here, our objective was to examine the duodenal microbiota between obese and normal volunteers using metagenomic techniques.We tested duodenal samples from five obese and five normal volunteers using 16S rDNA V6 pyrosequencing and Illumina MiSeq deep sequencing. The predominant phyla of the duodenal microbiota were Firmicutes and Actinobacteria, whereas Bacteroidetes were absent. Obese individuals had a significant increase in anaerobic genera (p < 0.001) and a higher abundance of genes encoding Acyl-CoA dehydrogenase (p = 0.0018) compared to the control group. Obese individuals also had a reduced abundance of genes encoding sucrose phosphorylase (p = 0.015) and 1,4-alpha-glucan branching enzyme (p = 0.05). Normal weight people had significantly increased FabK (p = 0.027), and the glycerophospholipid metabolism pathway revealed the presence of phospholipase A1 only in the control group (p = 0.05).The duodenal microbiota of obese individuals exhibit alterations in the fatty acid and sucrose breakdown pathways, probably induced by diet imbalance.